Correlation of Micronutrient Intake to BMI in Elderly Prolanis Participants - Suryani Agustina Daulay; Andi Eka Yunianto; Hesti Yuningrum; Sutrio Sutrio (Media Ilmiah Kesehatan Indonesia, 2026)
Participants in the Chronic Disease Management Program (Prolanis) are at risk of impaired nutritional status due to metabolic changes, chronic diseases, and imbalanced nutrient intake. Micronutrients play a critical role in body metabolism and may influence Body Mass Index (BMI). This study aimed to analyze the association between micronutrient intake and BMI among Prolanis participants. A quantitative observational study with a cross-sectional design was conducted. The sample consisted of 42 Prolanis participants aged 42–76 years. Micronutrient intake was assessed using a 24-hour food recall, while BMI was calculated from body weight and height measurements. Data were analyzed univariately, bivariately using Pearson’s correlation test, and multivariately using logistic regression. The results showed that sodium, vitamin A, vitamin C, vitamin E, zinc (Zn), and manganese (Mn) were significantly associated with BMI, whereas copper (Cu) showed no significant association. Multivariate analysis indicated that vitamin C, Zn, and Mn were significantly associated with BMI, with Mn being the most dominant factor. These findings suggest that micronutrient intake, particularly vitamin C, Zn, and Mn, plays an important role in the nutritional status of Prolanis participants.